Productive Financing for Micro, Small and Medium Enterprises (MSMES): Efforts to Achieve the Sustainable Development Goals (SDGS) - Niu, Fitria Ayu Lestari; Sumendap, Priscilia Christina (Program Study Islamic Banking, Faculty of Economics and Bussiness Islam, State Islamic Institute of Manado (IAIN) Manado, 2024)
This study aims to describe the productive financing of Bank Syariah Indonesia for MSMEs as an effort to achieve the SDGs using a literature review approach on secondary data in the form of financial statements and supporting data. The data was processed through financial statement analysis techniques, SATF Value performance measurement, and studies on relevant articles and literature. The results on Amanah's performance with the responsibility indicator, show that financing growth in MSME customers fluctuates, especially in 2021-2023 due to the Covid-19 pandemic. However, BSI continues to strive to follow its commitment to provide opportunities and convenience in financing, especially in the MSME sector. BSI has disbursed financing to MSMEs amounting to IDR 47.72 trillion or grew 14.54% annually. BSI also expands access to sharia financing, including through BSI Agen which resulted in 4.8 million transactions with a transaction volume of Rp 11 trillion, the MSME Center to increase the capacity and capability of MSMEs which has distributed financing of Rp 39.08 billion to more than 3,281 MSMEs fostered by BSI. BSI also has a platform namely the Digital Salam Portal to make it easier for the public to apply for microfinance digitally, to meet all business and investment needs, and provides financing for entrepreneurs at various levels of business, ranging from the micro level to corporations. BSI realizes that productive financing in the MSME sector has a huge role in realizing the SDGs, especially in the Decent Work and Economic Growth Target.